O projeto político-pedagógico no sistema de educação do município de São Paulo - Silva, Gabriel Blumel Fontan (2017)
The objective of this dissertation is to understand the political pedagogical projects (PPPs) in the education system of the City of Sao Paulo. In spite of the concepts of Ilma Passos Veiga, ―emancipating political pedagogical project" and ―technical regulatory political pedagogical project", sought to estimate the proportion of these two types of PPPs on the mentioned education system. The hypothesis was that the political pedagogical project of the municipal system in Sao Paulo are predominantly regulatory and technical because they express a fragmented vision of the school reality. Bibliographic analysis and review of related legislation conducted the survey, in addition to the documentary analysis of 18 political pedagogical projects from a Regional Board of the Municipal Secretary of Education of the City of Sao Paulo. The data are organized and presented in summary tables. The results show that the political pedagogical projects are not meant to be read because, notwithstanding do not indicate parameters of ideas, include topics, diagnosis and actions, and do not show, mostly, information about participation of parents, students, teachers and docent staff in the conception process of the PPP, being characterized as a formality negotiated between administrators. Regional leaders of education (appointed by the Municipal Secretary of Education), when homologating these PPPs, end up endorsing them. The actions provided in the various documents resemble each other, constituting what Veiga calls "regulators boards", which expose school managers’ interest in exert technical control, denying the politics and incurring moral valuation on the teacher’s performance and in student's stereotyping. On the other hand, ―emancipating‖ traces were found in two schools PPPs